PENGARUH PEMBERIAN DOSIS PAKAN CAMPURAN (CACING TANAH DENGAN PELLET) TERHADAP LAJU PERTUMBUHAN IKAN MAS KOKI (CARASSIUS AURATUS): The Effect Of Mixed Feed Dose (Earthworm With Pellet) On The Growth Rate Of Golden Gold (Carassius auratus) - Sukomo, Sukomo; Nufus, Chairun; Tarmizi, Azhari (Al-Qalbu: Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to determine the effect of mixed feed doses (earthworms and pellets) on the growth of goldfish (Carassius auratus). The method used in this study is the "experimental" method with a Completely Randomized Design (CRD). The number of treatments was 3 with each treatment repeated 4 times, so that 12 (twelve) experimental plots were obtained. The results of the measurement of the average weight growth rate (Growth Rate/GR) per goldfish (Carassius auratus) until the end of the study varied, namely for treatment X1 it had an average weight of 8.51 grams/tail, in treatment X2 it had an average of 7.69 grams/tail while in treatment X3 it had an average of 7.81 grams/tail. The weight growth of goldfish (Carassius auratus) seeds in each treatment showed that treatment X1 with X2 (8.15> BNT = 6.58) and X1 with X3 (7.01> BNT = 6.58) were significantly different (significant) while treatment X2 with X3 (1.15 < BNT = 6.58) showed no significant difference (non-significant). Measurement of water quality during the study were: average temperature 27.83oC, average pH 7.06, average dissolved oxygen (DO) 4.3 ppm